Marxism, cultural studies and sport [ - Carrington, Ben , 1972-; McDonald, Ian , 1965- (London New York : Routledge, 2009)
'Marxism, Cultural Studies and Sport' aims to contribute to the critical analysis of sport in society by joining together Marxist and Cultural Studies approaches in one volume, so as to reveal the underlying structures of power present in contemporary sporting cultures.
1. Marxism, Cultural Studies and sport: The key debates -- 2. Political economy, commodification and sport -- 3. The sporting poetics of class, race and gender -- 4. Key concepts, critical theorists
Description based on print version record
Includes bibliographical references and index
Keywords: Philosophy, Marxist; Sports and state; Sports -- Social aspects